The cook you want to be : everyday recipes to impress - Baraghani, Andy (Lorena Jones Books, an imprint of Ten Speed Press, 2022)
"In more than 100 recipes, Baraghani shows home cooks on how to hone their own cooking styles by teaching the techniques and unexpected flavor combinations that maximize flavor in minimal time"--